Analisa Tingkat Kelayakan Usability Marketplace Rumah Digital Berbasis System Usability Scale - Alfiyan, Faruk; Budiarto, Sony Panca (UNIVERSITAS RAHARJA, 2024)
The sustainability of the benefits of a system is a major factor that software developers should pay attention to. No matter how sophisticated the technology of the software system that is built, if users find it difficult to use it, it is certain that the goals and benefits to be achieved in the development of a software system will not be achieved. This is because users will not be interested in using the software system. To anticipate the emergence of these problems, it is necessary to conduct an initial analysis to find out whether the software system built already has a level of usability that is easy to use by users or not. One method to analyze the level of usability is the SUS (System Usability Scale) method. The stages of the SUS method consist of selecting respondents, data collection, score calculation and scale interpretation. This study aims to obtain usability level data from the use of the Rumah Digital marketplace. From this usability data, a conclusion will be obtained, whether the system that has been built has met the expectations of its users or not.